Formulasi dan Evaluasi Gel Pengharum Serai Wangi dengan Kombinasi Basis Karagenan, Xanthan Gum, dan HPMC - Anggraini, Windi; Salman, Salman; Febriani , Yessi; Indriana , Meutia; Muzakkir, Muzakkir (Journal of Pharmaceutical and Sciences, 2026)
Background: Unpleasant odors in bathroom areas are a common hygiene problem that requires practical and environmentally friendly solutions. Citronella oil (Cymbopogon nardus L. Randle) is known to contain active compounds with a distinctive aroma that has potential as a natural fragrance agent. However, an appropriate gel base is needed to maintain the stability and aroma retention of the preparation. Objective: This study aims to formulate and evaluate a bathroom fragrance gel from citronella oil with a combination of carrageenan, xanthan gum, and hydroxypropyl methylcellulose (HPMC) bases and to determine the concentration of citronella oil that produces the preparation with the best physical stability and aroma retention. Methods: This research was an experimental laboratory study. Citronella oil was formulated into gel preparations with four concentration variations (2.5%; 5%; 7.5%; and 10%) using a combination of carrageenan, xanthan gum, and HPMC bases. Evaluation of the preparations included organoleptic test, syneresis, liquid evaporation, preference test (hedonic), and aroma retention test for 15 days of storage. Data were analyzed statistically with a 95% confidence level. Results: The results showed that all formulas produced gels with good organoleptic characteristics (cloudy white color, characteristic citronella aroma, and semi-solid texture). The formula with 10% citronella oil concentration (F4) showed the best results with the lowest syneresis value (0.62%), the lowest liquid evaporation percentage (21.69%), and the highest remaining gel weight (92.03%). The preference test showed that F4 had the highest average value (4.25) in the like category, and the best aroma retention with a score range of 4.19-4.70 until day 15. Conclusion: The combination of carrageenan, xanthan gum, and HPMC bases can produce physically stable bathroom fragrance gel preparations. The formula with 10% citronella oil concentration (F4) is the best formulation and has the most potential to be developed as a natural bathroom fragrance product.